2021
DOI: 10.1016/j.chemphyslip.2021.105113
|View full text |Cite
|
Sign up to set email alerts
|

Cineole-containing nanoemulsion: Development, stability, and antibacterial activity

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…formulations indicating enhanced physical stability of these nanoscale colloidal emulsions (Gupta et al 2016;Lima et al 2021;Marhamati et al 2021;Ravera et al 2021). Such finding could be explained by a better packing of HCO-40 and SMO or HCO-40 and SIS at oil-water interfaces leading to a higher interfacial surfactant load and consequently optimum curvature and lower interfacial tension.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…formulations indicating enhanced physical stability of these nanoscale colloidal emulsions (Gupta et al 2016;Lima et al 2021;Marhamati et al 2021;Ravera et al 2021). Such finding could be explained by a better packing of HCO-40 and SMO or HCO-40 and SIS at oil-water interfaces leading to a higher interfacial surfactant load and consequently optimum curvature and lower interfacial tension.…”
Section: Resultsmentioning
confidence: 91%
“…However, these methods require substantial energy input density to form small droplets, yet most mechanical energy generated may be dissipated as heat. On the other hand, low-energy or thermodynamic methods rely on the spontaneous generation of nanodroplets simply by changing environmental conditions (e.g., temperature) or some formulation parameters, such as concentration and type of surfactant and/or oil, and oil-water ratio (Guo et al 2020;Gupta et al 2016;Helgeson 2016;Lima et al 2021;Meng et al 2021;Panigrahi et al 2019). The main low-energy methods of nanoemulsion formation include phase inversion composition, phase inversion temperature, emulsion phase inversion, and spontaneous emulsification (Komaiko and McClements 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, 1,8-Cineol is expelled from the lungs and can unfold its anti-inflammatory effects in the respiratory tract and the mucosal tissues, which has been monitored by real-time breath gas analysis using online proton-transfer-reaction mass spectrometry (PTR-MS) [25] (Figure 2). In a recent publication, the oral application of 1,8-Cineol con- The bioactivity of 1,8-Cineol is known to be rather limited due to its low aqueous solubility and stability; therefore, a regular ongoing administration is required [18]. The metabolization of 1,8-Cineol is maintained by the cytochrome P450 system in the mammalian liver [19,20] and the associated metabolites (2-hydroxy-, 3-hydroxy-, 7-hydroxyand 9-hydroxy-1,8-Cineol) can be detected accordingly in plasma and urine samples following the uptake of 1,8-Cineol [21].…”
Section: Origin Pharmacokinetics and Systemic Distributionmentioning
confidence: 99%
“…The present study revealed new insights into the distribution of 1,8-Cineol in the human body after oral administration and hint to a direct anti-inflammatory effect of 1,8-Cineol on site in nasal polyps of CRSwNP patients. The bioactive effects of 1,8-Cineol are known to be limited due to its low aqueous solubility and stability 33 . Different well-known 1,8-Cineol containing medications are applied orally as enteric coated capsules and evolve their curative effects after their passage through the stomach within the small intestine.…”
Section: Discussionmentioning
confidence: 99%